Fertility Desires and Intentions among HIV-Positive Women during the Post-natal period in Uganda - Gutin, Sarah A.; Namusoke, Fatuma; Shade, Starley B.; Mirembe, Florence (African journal of reproductive health, 2014)
This study describes the fertility intentions and discusses the potential reproductive health needs of post-natal HIV-infected Ugandan women. HIV-infected mothers attending post-natal services in Kampala, Uganda participated in this cross-sectional study using structured interviewer administered questionnaires. Descriptive statistics and logistic regression models were used to identify predictors of desire for more children. Among 403 participants, 35% desired more children. Of these, 25% wanted another child within 2 years and 75% within 3 years or more. In multivariable analyses, believing that one’s partners wanted more children (OR=2.44; 95% CI = 1.30, 4.59) was associated with the desire for future children while having more living children was negatively associated with the desire for future children (OR=0.08; 95% CI = 0.02, 0.39). A minority of women desired future pregnancies, and most wanted to delay pregnancy for 3 years. These women are in need of family planning (FP) methods to meet stated desires to delay or end future pregnancies. Perceived partner desire for children also impacts on women’s fertility intentions, highlighting the importance of engaging men during the post-natal period
Keywords: Fertility intentions; Desire for children; Post-natal women; HIV; Reproductive health; Contraception